1988
DOI: 10.1073/pnas.85.8.2613
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cDNAs encoding desmosomal plaque proteins: evidence that bovine desmoplakins I and II are derived from two mRNAs and a single gene.

Abstract: Desmoplakins (DPs) I and II (%240 and -210 kDa) are major components of the internal portion of the desmosomal cytoplasmic plaque. Desmosomes play a crucial role in cell-cell adhesion and serve as specific attachment sites for cytoplasmic intermediate riaments. Although DP-I and -II are closely related molecules, their structure (i.e., amino acid or DNA sequence) has not been determined. In addition, it is not known whether these proteins are derived from one or more genes or whether they result from posttrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Desmoplakin I has been found in all desmosomes studied (13,18), whereas DP II has been found predominantly, but not exclusively, in stratified squamous epithelia (19). Overlapping cDNA clones encoding two major domains of the human desmoplakins have been identified (4), and suggest that DP I and II are encoded by separate mRNAs derived from a single gene (5 Although we have previously reported that passive transfer of whole immunoglobulin fractions from patients with paraneoplastic pemphigus into neonatal mice can induce cutaneous and esophageal acantholysis (cell-cell detachment, 1, 2), the role of the autoantibodies that are directed specifically against the desmoplakins in the induction of lesions is not known. Any speculation that they might be causative is tempered by the fact that the desmoplakins are intracellular proteins with no transmembrane or extracellular domains, and it is not clear how serum autoantibodies could bind to and presumably compromise the function of such intracellular antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desmoplakin I has been found in all desmosomes studied (13,18), whereas DP II has been found predominantly, but not exclusively, in stratified squamous epithelia (19). Overlapping cDNA clones encoding two major domains of the human desmoplakins have been identified (4), and suggest that DP I and II are encoded by separate mRNAs derived from a single gene (5 Although we have previously reported that passive transfer of whole immunoglobulin fractions from patients with paraneoplastic pemphigus into neonatal mice can induce cutaneous and esophageal acantholysis (cell-cell detachment, 1, 2), the role of the autoantibodies that are directed specifically against the desmoplakins in the induction of lesions is not known. Any speculation that they might be causative is tempered by the fact that the desmoplakins are intracellular proteins with no transmembrane or extracellular domains, and it is not clear how serum autoantibodies could bind to and presumably compromise the function of such intracellular antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Their sequence and structure are known (3,4) and desmoplakin II is apparently a product of alternate splicing of the desmoplakin I transcript (5). Desmoplakin I has a M, = 250,000 in SDS-PAGE and a calculated mol wt of 201,000.…”
Section: Introductionmentioning
confidence: 99%
“…1D). Later, K. Green and her group determined that desmoplakins I and II are two splice mRNA forms derived from the same gene and that this large protein presents a very special organization with a near-aminoterminal plakin domain, a central coiled-coil region, and a so-called plakin-repeat domain in the carboxy-terminal portion (Green et al 1988(Green et al , 1990Virata et al 1992;Godsel et al 2004), so to say the prototype of what later was termed the "plakin family" of proteins (Ruhrberg and Watt 1997). The identification of the desmoplakins was soon followed by the localization of epidermaltype desmosomal proteins and glycoproteins in various cell types and species, although not in all cells that were known to contain true desmosomes (cf.…”
Section: Hard-core Anchors Of Cytoskeletal Elements: the Desmosomesmentioning
confidence: 99%
“…Initial cloning studies used antibodies to desmosomal components or degenerate oligonucleotide probes derived from peptide sequencing data to screen cDNA libraries (Green et al, 1988;Cowin et al, 1986;Goodwin et al, 1990). In 1989, Franke et al (1989) published the fi rst human sequence encoding a desmosomal protein, plakoglobin (abbreviated here as PG, offi cial gene symbol-JUP ).…”
Section: Identification Of Genes Encoding Desmosomal Componentsmentioning
confidence: 99%